Контроль в сфері державних закупівель та вплив його результатів на ефективність здійснення процедур закупівель - Заєць, Н. М.; Zaiets, N. (КНТУ, 2016)
Розглянуто види фінансового контролю, що застосовуються в сфері публічних (державних) закупівель. Проаналізовано показники перевірок публічних (державних) закупівель та розглянуто реалізацію їх результатів. Досліджено вплив результатів перевірок публічних (державних) закупівель на ефективність проведення процедур закупівель. Обґрунтовано необхідність реформування контролю у вигляді перевірок публічних (державних) закупівель з метою надання йому механізмів впливу на виправлення порушень в ході процедур закупівель без їх відміни, що дозволить підвищити ефективність їх здійснення. The purpose of this work is to investigate the procedure of control in Ukraine for the implementation of public (government) procurement and to analyze the results in terms of their impact on the effectiveness of procurement procedures. In the article the results of audits Ukraine in the implementation of public (government) procurement in recent years and analyzed their effectiveness regarding prevention of violations during the procurement process as well as their impact on the economy of public funds in the procurement. As a result, it is proved that the provision of financial control mechanisms improve the efficiency of procurement will have significant positive impact in terms of saving financial costs and time for procedures and provide the necessary requirements for procurement.
Control of public procurement and impact of its results on the effectiveness of the implementation of procurement procedures
Keywords: контроль; перевірка; публічні (державні) закупівлі; процедура закупівлі; замовник; ефективність закупівлі; control; inspection; public (government) procurement; purchase; customer; purchasing efficiency